Rapid Detection of Human Torque Teno Viruses Using High-Resolution Melting Analysis - Spandole S; Cimponeriu D; Toma M; Radu I; Ion D.A. (Balkan Journal of Medical Genetics, 2013)
Torque teno viruses (TTVs) are recently discovered DNA viruses, with heterogeneous genomes, highly prevalent in populations worldwide. The species that infect humans are Torque teno virus (TTV), Torque teno midi virus (TTMDV) and Torque teno mini virus (TTMV). High-resolution melting analysis (HRMA) is a sensitive and effective method for genotyping and mutation scanning. Up to now, HRMA has not been utilized for detection of TTVs.